Case report: A cystic capillary hemangioma located at the conus medullaris mimicking hemangioblastoma - Sun, Jiachen; Li, Jiuhong; Ayi, Ziba; Yang, Feilong; Hu, Junlin; Hui, Xuhui; Chen, Haifeng; He, Jiaojiang (Frontiers in Neurology, 2024)
Capillary hemangiomas, usually found in skin and mucosal tissues, are rarely encountered within the spinal cord, presenting a significant diagnostic challenge. We report a rare case of intradural extramedullary capillary hemangioma at the conus medullaris in a 66-year-old female patient. Our initial diagnosis leaned towards a cystic hemangioblastoma based on MRI findings due to the presence of cystic formation with an enhanced mural nodule. However, surgical exploration and subsequent pathological examination revealed the lesion as a capillary hemangioma. To the authors’ knowledge, this case may represent the first documented instance of a spinal capillary hemangioma that mimics a cystic hemangioblastoma.